Cost and Cost Driver Analysis of Anterior Cruciate Ligament Reconstruction Using Time-Driven Activity-Based Costing: Bone-Tendon-Bone Autograft Versus Hamstring Autograft. Issue 4 (11th October 2022) - Huyke-Hernández, Fernando A.; Siljander, Breana; Flagstad, Ilexa; Only, Arthur; Parikh, Harsh R.; Tompkins, Marc; Nelson, Bradley; Kweon, Christopher; Cunningham, Brian
Abstract : Background: As health care transitions toward value-based care, orthopaedics has started to implement time-driven activity-based costing (TDABC) to understand costs and cost drivers. TDABC has not previously been used to study cost drivers in anterior cruciate ligament reconstruction (ACLR). The purpose of this study was to use TDABC to (1) calculate bone-tendon-bone (BTB) and hamstring ACLR total costs of care and (2) evaluate the impact of graft choice and other factors on ACLR costs. Methods: Data were collected from electronic medical records for primary ACLR from the institutional patient-reported outcome registry between 2009 and 2016 in 1 ambulatory surgery center. Patients receiving allograft, revision ACLR, or concomitant meniscal repair or ligament reconstruction were excluded. The total cost of care was determined using TDABC. Multivariate regression analysis was conducted between ACLR cost and group characteristics. Results: A total of 328 patients were included; 211 (64.3%) received BTB autograft and 117 (35.7%) received hamstring autograft. The mean cost was 2, 865.01 ± 263.45 (95% confidence interval: 2, 829.26, 2, 900.77) for BTB ACLR versus 3, 377.44 ± 320.12 (3, 318.82, 3, 436.05) for hamstring ACLR (p < 0.001). Operative time was 103.1 ± 25.1 (99.7, 106.5) minutes for BTB ACLR versus 113.1 ± 27.9 (108.0, 118.2) minutes for hamstring ACLR (p = 0.001). The total implant cost was 270.32 ± 97.08 (257.15, 283.50) for BTB ACLR versus 587.36 ± 108.78 (567.44, 607.28) for hamstring ACLR (p < 0.001). Hamstring graft (p = 0.006) and suspensory fixation on the femoral side (p = 0.011) were associated with increased costs. Conclusions: The mean cost of care and operative time for BTB autograft ACLR are less than those for hamstring autograft ACLR. Operative time, implant choice, and graft choice were identified as modifiable cost drivers that can empower surgeons to manage primary ACLR costs while maximizing the value of the procedure. Level of Evidence: Economic and Decision Analysis Level IV . See Instructions for Authors for a complete description of levels of evidence.